Remoção de sílica reativa de bauxita por flotação - Silva, Gustavo Victor Batista E (2023)
The objective of this work was to contribute to the development of a strategy of reverse cationic flotation of kaolinite from bauxite using several bauxite samples from Juruti- PA of the Alcoa company. The samples were characterized regarding their chemical composition by determining the content of Usable Aluminum (AA) and Reactive Silica (RS), the mineralogical composition, and the granulometric and granulochemical distributions. Flotation experiments were initially performed for the selection of collectors, depressants and dispersants. Then the most promising reagents were used in flotation tests with the samples with higher amount of fines and RS content. In the most successful conditions, the flotation reduced the RS content from 19.02% in the feed to 6.37%. The most promising reagents were the F-EDA at 200g/t (alkyl etheramine) as kaolinite collector, the corn starch (AMD) at 400g/t as gibbsite depressant, and the NO149 (polyacrylamide) at 200g/t as dispersant at pH > 9.0. The reduction in the solids content improved the flotation of bauxites with large amount of fine particles. Flotation was not efficient to reduce the RS content of the tailing sample. Compared to the physical concentration by hydrocycle that currently occurs in the plant, the concentration by flotation, still in batch, presented twice the mass recovery. The work indicates the possibility of using the flotation technique in the operation of Juruti.